CULTURAL HYBRIDITY AS THE IMPACT OF BRITISH COLONIALISM IN ACHEBE’S THINGS FALL APART: cultural hybridity as the impact of british colonialism in Achebe's things Fall apart - Yuliana Sari, Putri; Ruly Indra Darmawan (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2024)
This study deals with the novel entitled Things Fall Apart which is create by a well-known Nigerian writer Chinua Achebe to sees the portraying of the relationship between British colonialism and cultural hybridity. The entire novel portrays Igbo society with specificity and sympathy and examines the effects of British colonialism from an African perspective. The objectives of this study is to identify the way the author explain the impact of British colonialism in Igbo society and create cultural hybridity phenomena which include religion or believe system, educational system and law or politic system among Igbo society. Keywords: Things Fall Apart, British colonialism, Cultural hybridity, African